Fluorescent single-digit detonation nanodiamond for biomedical applications. (8th May 2018) - Nunn, Nicholas; d'Amora, Marta; Prabhakar, Neeraj; Panich, Alexander M; Froumin, Natalya; Torelli, Marco D; Vlasov, Igor; Reineck, Philipp; Gibson, Brant; Rosenholm, Jessica M; Giordani, Silvia; Shenderova, Olga
Abstract: Detonation nanodiamonds (DNDs) have emerged as promising candidates for a variety of biomedical applications, thanks to different physicochemical and biological properties, such as small size and reactive surfaces. In this study, we propose carbon dot decorated single digit (4–5 nm diameter) primary particles of detonation nanodiamond as promising fluorescent probes. Due to their intrinsic fluorescence originating from tiny (1–2 atomic layer thickness) carbonaceous structures on their surfaces, they exhibit brightness suitable for in vitro imaging. Moreover, this material offers a unique, cost effective alternative to sub-10 nm nanodiamonds containing fluorescent nitrogen-vacancy color centers, which have not yet been produced at large scale. In this paper, carbon dot decorated nanodiamonds are characterized by several analytical techniques. In addition, the efficient cellular uptake and fluorescence of these particles are observed in vitro on MDA-MD-231 breast cancer cells by means of confocal imaging. Finally, the in vivo biocompatibility of carbon dot decorated nanodiamonds is demonstrated in zebrafish during the development. Our results indicate the potential of single-digit detonation nanodiamonds as biocompatible fluorescent probes. This unique material will find application in correlative light and electron microscopy, where small sized NDs can be attached to antibodies to act as a suitable dual marker for intracellular correlative microscopy of biomolecules.